Colombia - National Level Public Financial Management and Procurement Report : Status of the Public Financial Management and Procurement System - World Bank; Inter-American Development Bank (World Bank, 2012)
This Public Financial Management Performance Report (PFMPR) analyzes the performance of Colombia's public financial management (PFM) institutions, systems and processes. It documents areas where performance is close to or follows international good practice, as well as opportunities to further enhance PFM contribution to the goals of strengthening fiscal discipline, enabling more efficient allocation of resources, increasing operational efficiency, and fostering transparency. It is expected that the identified opportunities will strengthen further the Government of Colombia's programs of continuous PFM improvement, as provided for under the National Development Plan pillar regarding a state at the service of its citizens: efficient and effective Government. The main challenges cited in the report could also be an important reference to future development plans and PFM reforms. Ensuring the sustainability and trajectory of PFM programs becomes even more critical in the context of public expenditure policies to deal with the current international economic crisis. The study is based on the 28 high-level indicators and 69 individual dimensions that compose the PFM performance measurement framework. Each indicator seeks to measure performance of a key PFM element against a scale from A to D. The highest score is warranted for an individual indicator if the core PFM element meets the relevant objective in a complete, orderly, accurate, timely and coordinated way, based on existing good international practices.